Cement paste system as well as preparation method and application thereof
By using cement slurry system prepared by raw materials such as graphite slag, the cement slurry system in cementing projects is solved, and a low-cost and efficient cementing slurry system is achieved, with good thermal conductivity and environmental protection characteristics.
Patent Information
- Application Number
- CN202311227525.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-21
- Publication Date
- 2025-03-21
AI Technical Summary
In cementing projects, facing complex geological conditions and high cost problems, the existing cement slurry system is difficult to meet the requirements of high temperature strength stability, high toughness and low thermal conductivity, and there are also problems of high costs and environmental pollution.
Graphite slag is used as the main raw material, combined with water-reducing agent, activation material, reinforcement, floating beads and water, to prepare a cement slurry system, which includes 10-50% graphite slag, 1-2% water-reducing agent, 0.1-1% activation material, 0-20% reinforcement, 15-25% floating beads and 30-70% water.
The cement slurry system has good thermal conductivity, meets the low density, low temperature and early strength requirements of cementing heat conduction cement slurry system, and has the advantages of low water loss, easy pumping and simple operation, which fully meets the on-site cementing requirements. At the same time, due to the use of industrial waste and power plant waste, it has the characteristics of low cost and environmental protection.
Smart Images

Figure CN119661179A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of drilling fluid, and in particular relates to a cement slurry system and a preparation method and application thereof. Background Art
[0002] With the gradual deepening of oil and gas exploration and development, the development of unconventional and complex oil and gas resources has been increasingly strengthened. The geological conditions of oil and gas reservoirs faced by cementing operations have become more complex. Abnormally high-pressure gas, high-pressure salt water layers, low-pressure leaky formations, abnormally low-pressure oil and gas layers, and high-temperature and high-pressure formations are often encountered during cementing. Therefore, it is necessary to use corresponding cement varieties and select appropriate admixtures to ensure safe construction and project quality. Faced with the severe situation of continued low oil prices, the research and development of low-cost high-strength cement slurry systems is an effective way to reduce cementing costs and achieve energy conservation and efficiency improvement.
[0003] The application of graphite slag cement-based materials can effectively solve the above problems. Graphite slag is an industrial waste material with low price. It can be used to prepare oil well cement slurry, which can save cement raw materials and reduce cementing costs. At present, domestic and foreign researchers have evaluated the applicability of graphite slag in building materials, mechanical property improvement or microstructural changes, but the research on changing the performance of cement-based materials with graphite slag is still in its infancy, and the research on adding graphite slag to cement for oil and gas well cementing has not been reported. There is a lack of relevant experience and information for reference in cementing engineering design and construction.
[0004] There is no shortage of patent records for cementing cement, for example: the patent with the invention name "A thermal conductivity cementing cement system for hot dry rock production wells" (application number 202011432234.5, application publication number CN 112321219 A), the thermal conductivity cementing cement system belongs to the technical field of cement slurry system, and is composed of the following raw materials by weight percentage: low hydration thermal cement or low calcium-silicon ratio cement 70-88%; high temperature strength stabilizer 10.5-25%; thermal conductivity material 1-8%; high temperature toughening agent 0.5-4%, effectively improving the high temperature strength stability, high toughness and low thermal conductivity of the cementing cement ring. The cementing cement system obtained in the present invention can meet the performance requirements of hot dry rock production wells for cementing cement at high temperature stability, high toughness and low thermal conductivity.
[0005] The invention name is "A thermal conductivity cement system for hot dry rock production wells" (application number 201710344089.7, application publication number CN 107216071 A). The present invention specifically relates to a thermal conductivity cement slurry for cementing the low-temperature section of a deep geothermal well and a preparation method thereof. The thermal conductivity cement slurry for cementing the low-temperature section of a deep geothermal well is prepared from the following raw materials in weight percentage: 15-25% oil well cement, 15-25% oil well ultrafine cement, 4-7% tungsten diselenide, 2-5% nano-silicon dioxide, 4-7% hollow glass microspheres, 1-4% early strength agent, 1-2% fluid loss reducer, 0.2-0.6% dispersant, 1-3% glass wool fiber, 5-10% silicate, and the balance is water. The preparation method thereof is as follows: oil well cement, oil well ultrafine cement, tungsten diselenide, nano silicon dioxide, hollow glass microspheres, early strength agent, fluid loss agent, dispersant and water are added in sequence, stirred until uniformly mixed, and then glass wool fiber and silicate are added in sequence, stirred until uniformly mixed. The thermal conductivity cement slurry for cementing low temperature section of deep geothermal well of the present invention has good thermal conductivity, and has the advantages of low density, early strength, low water loss, easy pumping, etc., and its various performance indicators fully meet the requirements of on-site cementing.
[0006] Introducing graphite slag into the research and development of cement can not only reduce the occupation of farmland and pollution to the surrounding environment, but also prevent soil erosion of graphite slag and avoid the pollution of air environment by dust generated during storage, which has huge social and economic benefits. The reuse of graphite slag instead of river sand can alleviate the urgent need for natural sand and gravel resources, reduce the cost of oil well cement, and conform to the development policy of "resource conservation and environmental friendliness". Therefore, it is of great significance to explore the application of graphite slag in cementing cement materials. Summary of the invention
[0007] In order to solve the above problems in the prior art, the present invention provides a cement slurry system and a preparation method and application thereof.
[0008] In the first aspect, the present invention proposes a cement slurry system, which, based on the mass of cement, also includes 10-50% of graphite slag, 1-2% of fluid loss reducer, 0.1-1% of activation material, 0-20% of reinforcing agent, 15-25% of floating beads and 30-70% of water.
[0009] As a specific embodiment of the present invention, based on the mass of cement, the cement slurry system also includes 20-30% graphite slag, 1-2% fluid loss reducer, 0.1-1% activation material, 0-20% reinforcing agent, 15-25% floating beads and 30-50% water.
[0010] As a specific implementation of the present invention, the cement is Grade G oil well cement.
[0011] As a specific embodiment of the present invention, the average particle size of the graphite slag is 20-30 μm, preferably 28.78 μm.
[0012] As a specific embodiment of the present invention, the activation material is a sodium silicate solution.
[0013] As a specific embodiment of the present invention, the fluid loss agent is an AMPS fluid loss agent; preferably, it is a SYJ-1 fluid loss agent.
[0014] As a specific embodiment of the present invention, the reinforcing agent is microsilicon, and the particle size of the microsilicon is 60-500 mesh.
[0015] As a specific embodiment of the present invention, the particle size of the floating beads is 50 to 800 meshes.
[0016] The above raw materials in the present invention can be prepared in-house or commercially available, and the present invention is not particularly limited thereto.
[0017] In a second aspect, the present invention provides a method for preparing the cement slurry system described in the first aspect, comprising: uniformly mixing cement, graphite slag, a fluid loss reducer, an activating material, a reinforcing agent, floating beads and water to obtain the cement slurry system.
[0018] In a third aspect, the present invention provides application of the cement slurry system described in the first aspect or the cement slurry system prepared by the preparation method described in the second aspect in the field of well cementing.
[0019] Compared with the prior art, the present invention has the following beneficial effects:
[0020] The cement slurry system of the present invention has good thermal conductivity. In addition to meeting the requirements of low density and low-temperature early strength of the cementing heat conduction cement slurry system, its thermal conductivity is outstanding. It also has the advantages of low water loss, easy pumping and simple preparation and operation. Its various performance indicators fully meet the requirements of on-site cementing. The graphite slag used is industrial waste, and the floating beads are power plant waste. They are inexpensive and have the characteristics of being green, environmentally friendly and low-cost. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 The thermal conductivity test results of Example 1 and Comparative Example 1 of the present invention are shown in FIG. DETAILED DESCRIPTION
[0022] The present invention will be further described below in conjunction with specific embodiments, but they do not constitute any limitation to the present invention.
[0023] The specific information of the reagents used in the embodiments of the present invention is as follows:
[0024] The cement is Zhongchang G-grade HSR cement, produced by Zhongchang Cement Plant;
[0025] Graphite slag was from Shandong Obot Petroleum Co., Ltd., with an average particle size of 28.78 μm;
[0026] The fluid loss additive was from Shandong Obot Petroleum Co., Ltd., model SYJ-1;
[0027] The concentration of sodium silicate solution is 0.8%;
[0028] The source of the floating beads is Henan Weihui Chemical Co., Ltd., with an average particle size of 500 mesh;
[0029] The average particle size of microsilicon is 200 mesh.
[0030] Example 1
[0031] This embodiment provides a cement slurry system and a preparation method thereof, the specific details of which are as follows:
[0032] 100 parts by weight of cement; 25 parts by weight of graphite slag; 0.8 parts by weight of sodium silicate; 2 parts by weight of fluid loss reducer; 0.6 parts by weight of activating material; 10 parts by weight of floating beads; and 42 parts by weight of water are used to prepare cement slurry in accordance with GB / T10238-2015 standard.
[0033] The thermal conductivity of the cement slurry system obtained in Example 1 was tested, and the thermal conductivity was 2.39 W / m·k and the density was 1.41 g / cm 3 ,like Figure 1 shown.
[0034] Example 2
[0035] This embodiment provides a cement slurry system and a preparation method thereof, the specific details of which are as follows:
[0036] 100 parts by weight of cement, 20 parts by weight of graphite slag, 0.6 parts by weight of sodium silicate, 0.8 parts by weight of fluid loss reducer, 0.5 parts by weight of drag reducer, 12 parts by weight of microsilica, 10 parts by weight of floating beads and 50 parts by weight of water were uniformly mixed to obtain a cement slurry system.
[0037] Example 3
[0038] This embodiment provides a cement slurry system and a preparation method thereof, the specific details of which are as follows:
[0039] 100 parts by weight of cement, 30 parts by weight of graphite slag, 0.8 parts by weight of sodium silicate, 1.2 parts by weight of fluid loss reducer, 0.5 parts by weight of drag reducer, 12 parts by weight of microsilica, 10 parts by weight of floating beads and 50 parts by weight of water were uniformly mixed to obtain a cement slurry system.
[0040] Comparative Example 1
[0041] The comparative example provides Shengwei cement paste, which is composed of 100 parts by weight of cement; 2 parts by weight of fluid loss reducer; 0.5 parts by weight of drag reducer; 42 parts by weight of water, and the thermal conductivity is 1.15 W / m·k. Figure 1 shown.
[0042] Test Example 1
[0043] The cement slurry system obtained in Example 1 was subjected to density, water loss, strength, and pressure thickening test tests. The test results are shown in Table 1. The free liquid test showed that the free liquid volume was 0 after 2 hours, and the density difference between the top and bottom of the cement stone was less than 0.01 g / cm 3 The cement slurry system has good sedimentation and suspension stability, which can effectively ensure the uniformity and stability of the cement slurry during the waiting period and prevent the cement slurry from settling and causing oil, gas and water channeling. See Table 1.
[0044] Table 1
[0045] project Graphite slag cement slurry <![CDATA[Density g / cm 3 > 1.42 API water loss ml (60℃66.9MP6630m66) 40 Free liquid % 0 Pressure thickening time m66 (60℃630MP6625m66) 209 Compressive strength MP6 (60℃620.7MP66246) 18.36 Compressive strength MP6 (140℃620.7MP661686) 22.11
[0046] It can be seen from Table 1 that the water loss performance of the cement paste system is excellent. The compressive strength of cement paste 246 is 18.36MP6, and the 7d compressive strength is 22.11MP6 / 140℃×21MP6, which can fully meet the needs of the project.
[0047] Test Example 2
[0048] The thermal conductivity of the cement slurry system obtained in Example 1 and the cement slurry system obtained in Comparative Example 1 was tested. The thermal conductivity test results are as follows: Figure 1 As shown, the thermal conductivity coefficient of the conventional density cement paste of Comparative Example 1 at room temperature is 1.13 W / (m·K), and the thermal conductivity coefficient of the graphite cement slurry system of Example 1 is 2.37 W / (m·K). The lower the thermal conductivity coefficient, the worse the heat transfer effect and the better the thermal conduction effect. The thermal conductivity coefficients of graphite cement paste and conventional density cement paste are both less than 5 W / (m·K), indicating that both have good thermal conduction and heat insulation effects.
[0049] Test Example 3
[0050] The mechanical properties of the cement slurry system obtained in Example 1 were tested, and the test results are shown in Table 2:
[0051] Table 2
[0052]
[0053] The elastic modulus and Poisson's ratio of a material can characterize the material's ability to resist deformation within the elastic range. The lower the elastic modulus, the greater the material's ability to recover deformation within the elastic deformation range. The data in Table 2 show that the elastic modulus of the cement paste obtained in Example 1 after hardening is 8.98GP6, and the Poisson's ratio is close to 0.20, which has high strength and good mechanical deformation capacity.
[0054] Test Example 4
[0055] The cement slurry system obtained in Example 1 was subjected to basic performance tests, and the test results are shown in Table 3:
[0056] Table 3
[0057]
[0058] It can be seen from Table 3 that the density of the low-density cement slurry prepared by the present invention can be between 1.42 and 1.55 g / cm 3 The fluidity is between 22.5 and 23 cm, the slurry has good fluidity, the water loss is controlled within 50 ml, the thickening time is adjustable, and the comprehensive performance of the cement slurry is good.
[0059] In summary, the cement slurry system of the present invention meets the requirements of low density and low-temperature early strength of the cementing heat conduction cement slurry system, has outstanding thermal conductivity, and also has the advantages of low water loss, easy pumping, and simple preparation and operation. Its various performance indicators fully meet the requirements of on-site cementing. The graphite slag used is industrial waste, low in price, and has the characteristics of green environmental protection and low cost.
[0060] Any numerical value mentioned in the present invention, if there is only an interval of two units between any minimum value and any maximum value, includes all values from the minimum value to the maximum value each time increasing by one unit. For example, if the amount of a component, or the value of a process variable such as temperature, pressure, time, etc. is declared to be 50-90, in this specification it means that 51-89, 52-88... and 69-71 and 70-71 are specifically listed. For non-integer values, 0.1, 0.01, 0.001 or 0.0001 can be appropriately considered as a unit. These are just some specially specified examples. In this application, in a similar manner, all possible combinations of numerical values between the listed minimum and maximum values are considered to have been disclosed.
[0061] It should be noted that the embodiments described above are only used to explain the present invention and do not constitute any limitation to the present invention. The present invention has been described with reference to typical embodiments, but it should be understood that the words used therein are descriptive and explanatory words, rather than restrictive words. The present invention may be modified as specified within the scope of the claims of the present invention, and the present invention may be revised without departing from the scope and spirit of the present invention. Although the present invention described therein relates to specific methods, materials and embodiments, it does not mean that the present invention is limited to the specific examples disclosed therein, on the contrary, the present invention can be extended to all other methods and applications with the same functions.
Claims
1. A cement slurry system, characterized in that: Based on the cement mass, the cement slurry system also includes 10-50% of graphite slag, 1-2% of fluid loss reducer, 0.1-1% of activation material, 0-20% of reinforcing agent, 15-25% of floating beads and 30-70% of water.
2. The cement slurry system according to claim 1, characterized in that: Based on the mass of cement, the cement slurry system also includes 20-30% of graphite slag, 1-2% of fluid loss reducer, 0.1-1% of activation material, 0-20% of reinforcing agent, 15-25% of floating beads and 30-50% of water.
3. The cement slurry system according to claim 1 or 2, characterized in that: The cement is Grade G oil well cement.
4. The cement slurry system according to any one of claims 1 to 3, characterized in that: The average particle size of the graphite slag is 20-30 μm, preferably 28.78 μm.
5. The cement slurry system according to any one of claims 1 to 4, characterized in that: The activation material is a sodium silicate solution.
6. The cement slurry system according to any one of claims 1 to 5, characterized in that: The fluid loss agent is an AMPS fluid loss agent, preferably a SYJ-1 fluid loss agent.
7. The cement slurry system according to any one of claims 1 to 6, characterized in that: The reinforcing agent is microsilicon, and the particle size of the microsilicon is 60-500 meshes.
8. The cement slurry system according to any one of claims 1 to 7, characterized in that: The particle size of the floating beads is 50 to 800 meshes.
9. A method for preparing the cement slurry system according to any one of claims 1 to 8, characterized in that: The method comprises: uniformly mixing cement, graphite slag, a fluid loss reducer, an activating material, a reinforcing agent, floating beads and water to obtain the cement slurry system.
10. Use of the cement slurry system according to any one of claims 1 to 8 or the cement slurry system prepared by the preparation method according to claim 9 in the field of well cementing.
Citation Information
Patent Citations
Thermal insulation cement slurry for well cementation of low-temperature sections of deep geothermal wells and preparation method thereof
CN107216071A
Thermal insulation well cementing cement system for hot dry rock production well
CN112321219A
A cementing system for thermal insulation of hot dry rock production wells
CN112321219B
Cited By
High-performance well cementation cement system for deep geothermal development
CN120590100A